2019
DOI: 10.1021/acs.biomac.9b01377
|View full text |Cite
|
Sign up to set email alerts
|

Structural Order in Cellulose Thin Films Prepared from a Trimethylsilyl Precursor

Abstract: Biopolymer cellulose is investigated in terms of the crystallographic order within thin films. The films were prepared by spincoating of a trimethylsilyl cellulose precursor followed by an exposure to HCl vapors; two different source materials were used. Careful precharacterization of the films was performed by infrared spectroscopy and atomic force microscopy. Subsequently, the films were investigated by grazing incidence X-ray diffraction using synchrotron radiation. The results showed broad diffraction peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Subsequently, NCs have appeared promising as the heat spreading materials. There are several polymorphs of crystalline cellulose (I, II and III) [42,43]. Cellulose I is the crystalline cellulose that is naturally produced by various organisms and it is often referred to as "native" or "natural" cellulose.…”
Section: Heat Conduction In Nanocellulosesmentioning
confidence: 99%
“…Subsequently, NCs have appeared promising as the heat spreading materials. There are several polymorphs of crystalline cellulose (I, II and III) [42,43]. Cellulose I is the crystalline cellulose that is naturally produced by various organisms and it is often referred to as "native" or "natural" cellulose.…”
Section: Heat Conduction In Nanocellulosesmentioning
confidence: 99%
“…introduced LiCl/DMAc as a nonderivatizing solvent for cellulose in the early 1980s and since then it has become the standard solvent for gel permeation chromatography (GPC) analysis of the molecular mass of cellulosic materials. , The mechanism of cellulose dissolution in this solvent system has been studied by using nuclear magnetic resonance (NMR), ,, and it was found that LiCl/DMAc breaks the intermolecular interactions resulting in a molecular solution of cellulose. Previous work has focused on the cellulose dissolution mechanism. , There are a few recent studies where the supramolecular rearrangements in cellulose thin films were established by grazing incidence small-angle X-ray scattering (GISAXS) measurements during the conversion of trimethylsilyl cellulose to cellulose via HCl vapor hydrolysis, , and the effect of heat treatment on its structure and morphology was established . GISAX was also employed by Roth et al .…”
mentioning
confidence: 99%
“…This exposure cleaves off the silyl groups leaving a rather amorphous cellulose thin film with only short-range ordered cellulose molecules. 39 Since the vapor pressure of the solvent during spin coating can affect the film structure, two different TMSC derivatives featuring a different solubility behavior (CHCl 3 and THF) and molecular mass ( M w : 130 vs 120 kDa) were selected to prepare cellulose thin films. In the following, the cellulose films derived from TMSC A are denoted as Cell A whereas those from TMSC S are denoted as Cell S .…”
Section: Resultsmentioning
confidence: 99%
“…3 to 6 nm definitely influence water uptake into the films. 39 Furthermore, the different vapor pressures of the employed solvents may contribute to this effect. The necessity to induce a third layer for the description of the Cell A films, also point the distinction of the film structures between Cell A and Cell S .…”
Section: Resultsmentioning
confidence: 99%